Analysis of Mercury in Fish, North Sumatera Indonesia by Atomic Absorption Spectrophotometer - Purba, Jhan Saberlan Purba; Silalahi, Jansen (Asian Journal of Pharmaceutical Research and Development, 2020)
The maximum level of mercury permitted in fish by BPOM RI is 0.5 mg/kg. This study was conducted to determine the level of mercury in fish often consumed in Medan Indonesia. Fish samples were collected from 7 traditional fish market outlets and 1 supermarket in Medan in December 2019. Fish samples were dried using an oven at 1030C untill a constant dry weight was attained. Then, the digestionprocess was carried out using concentrated nitric acid and perchloric acid. Determination of mercury level was carried out using CV-AAS method with 900 H Perkin Elmer atomic absorption spectrophotometer equipped with MHS-15 (Mercury Hidride System). The results showed that the level of mercury in pelagic fish was found significantly in yellowfin tuna (Thunnusalbacares) of 27.3865 ± 0.3326 µg/kg; mackerel tuna (Euthynnusaffinis) of 17.8570 ± 0.0121 µg/kg; skipjack tuna(Katsuwonuspelamis) of 17.4507 ± 1.5893 µg/kg; spanish mackerel (Scomberomoruscommersonii) of 10.5767 ± 0.1862 µg/kg; grouper (Epinepheusfuscoguttatus) of 9.9736 ± 0.9115 µg/kg; mackerel (Rastreligerkanagurta) of 6.5364 ± 0.1935 µg/kg and dumersal fish were found significantly in red snapper (Lutjanuscampechanus) of 14.0966 ± 0.8555 µg/kg; stingray(Dasyatissp) of 61.3146 ± 0.8149 µg/kg; ariid catfish (Arius thalassinus) of 13.2533 ± 0.7586 µg/kg; black pomfret(Parastromateusniger) of 10.7755 ± 0.4605 µg/kg; sardine(Sardinellasp) of 6.5464 ± 0.1036. The results showed that the larger fish has the higher mercury level. The level of mercury in these analyzed fish samples was below maximum level permitted by BPOM RI.